Implementation of In-Depth Learning through Historical Study Tours to Increase Elementary School Students' Learning Motivation - Anita Supriati Mutmainnah; Ninik Indawati; Cicilia Ika Rahayu Nita (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to describe and analyze the application of in-depth learning through historical study tours to improve the motivation to learn of fourth-grade elementary school students. The study used a qualitative, descriptive approach and was conducted at SDN Mulyorejo 1 in Malang City. The research subjects consisted of two teachers and six students, selected purposively. Data collection techniques were carried out through observation, interviews, and documentation, and were analyzed using an interactive analysis model with the stages of data reduction, data presentation, and conclusion drawing. The research results show that implementing in-depth learning through a historical study tour at Badut Temple can create more meaningful, contextual, and enjoyable learning. This activity increases student active engagement through direct observation, discussion, and interaction with resource persons. Furthermore, there is an increase in student learning motivation, as demonstrated by increased activity, curiosity, and enthusiasm in participating in the learning. This experiential learning also strengthens conceptual understanding and fosters character values such as responsibility, cooperation, and concern for cultural heritage. Thus, in-depth learning through historical study tours can be an effective strategy for increasing elementary school students' learning motivation, though its implementation requires careful planning, adequate time, and financial support.